High lymphocyte count during neoadjuvant chemoradiotherapy is associated with improved pathologic complete response in esophageal cancer. Issue 3 (September 2018) - Fang, Penny; Jiang, Wen; Davuluri, Rajayogesh; Xu, Cai; Krishnan, Sunil; Mohan, Radhe; Koong, Albert C.; Hsu, Charles C.; Lin, Steven H.
Abstract: Background and purpose: Neoadjuvant chemoradiation (nCRT) can reduce tumor infiltrating lymphocytes. We examined absolute lymphocyte count (ALC) nadir during nCRT for esophageal cancer (EC) and pathologic complete response (pCR). Materials and methods: Patients with stage I–IVA EC ( n  = 313) treated 2007–2013 with nCRT followed by surgery were analyzed. ALC was obtained before, during/weekly, and one month after CRT. pCR was defined as no viable tumor cells at surgery. High ALC was defined as nadir of ≥0.35 × 10 3 /μL (highest tertile). Comparison of continuous and categorical variables by pCR was assessed by ANOVA and Pearson's chi-square. Univariate/multivariate logistic regression was used to assess predictors of pCR and high ALC nadir. Results: Eighty-nine patients (27.8%) achieved a complete pathological response (pCR). For patients with pCR, median ALC nadir was significantly higher than those without (0.35 × 10 3 /μL vs 0.29 × 10 3 /μL, p  = 0.007). Patients maintaining high ALC nadir had a higher pCR rate (OR1.82, 95%CI 1.08–3.05, p  = 0.024). Predictors of high ALC included treatment with proton therapy vs. IMRT (OR4.18, 95%CI 2.34–7.47, p  < 0.001), smoking at diagnosis (OR2.80, 95%CI 1.49–5.25, p  = 0.001), early stage I–II disease (OR2.33, 95%CI 1.32–4.17, p  = 0.005), and SCC histology (OR3.70, 95%CI 1.01–14.29, p  = 0.048). Mean body dose (MBD) was inversely related to high ALC nadir (OR0.77 per Gy, 95%CI 0.70–0.84, p  < 0.001). Conclusion: A higher ALC level during nCRT is associated with a higher rate of pCR for esophageal cancer patients undergoing trimodality therapy.